2012
DOI: 10.1111/j.1348-0421.2012.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Different potency of bacterial antigens TLR2 and TLR4 ligands in stimulating mature mast cells to cysteinyl leukotriene synthesis

Abstract: The aim of study was to compare the potency of different bacterial antigens to induce rat mature mast cell to cysteinyl leukotriene (cysLT) generation. We examined Toll-like receptor (TLR)2 agonists, i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Recent reports have highlighted that other cells such as alveolar epithelial cells play an important role in innate defense to produce the chemokine CCL2 and also in the pathogenesis of mycobacterial infection (Chuquimia et al, 2012). Additionally, mast cells are activated by mycobacterial LAM to induce the generation of cysteinyl leukotriene through TLR2-NF-κB-dependent signaling (Bąbolewska et al, 2012). Together, these studies suggest that TLRs have a crucial role in the host immune responses against mycobacterial infection and that they are involved in not only immune cells but also other cells.…”
Section: Overview Of Tlrs In Mycobacterial Infectionmentioning
confidence: 99%
“…Recent reports have highlighted that other cells such as alveolar epithelial cells play an important role in innate defense to produce the chemokine CCL2 and also in the pathogenesis of mycobacterial infection (Chuquimia et al, 2012). Additionally, mast cells are activated by mycobacterial LAM to induce the generation of cysteinyl leukotriene through TLR2-NF-κB-dependent signaling (Bąbolewska et al, 2012). Together, these studies suggest that TLRs have a crucial role in the host immune responses against mycobacterial infection and that they are involved in not only immune cells but also other cells.…”
Section: Overview Of Tlrs In Mycobacterial Infectionmentioning
confidence: 99%
“…MCs are well accepted as highly competent cells for host defense against bacteria. For instance, several microbial products have been shown to stimulate MCs through TLR2 and TLR4 to generate various proinflammatory humoral factors, including lipid mediators, cytokines, and chemokines [11][12][13][14][15][16][17]. Mainly, these cells exert several mechanisms of direct bacterial killing like the ability to phagocytose and intracellular digestion via oxidative and nonoxidative route [18] or, irrespective of phagocytosis, to form extracellular traps (MCETs), which can entrap and eliminate various bacterial materials [19].…”
Section: Introductionmentioning
confidence: 99%
“…TLR ligation by its agonists induces the highly selective mast cell response. A number of studies have indicated that neither TLR2 nor TLR4 stimulation resulted in mast cell degranulation and preformed mediator release [5][6][7][8][9][10] but it induces synthesis of newly generated lipid mediators, including cysteinyl leukotrienes (cysLTs) [5,[7][8][9][10][11][12][13]. TLR2 and TLR4 ligation can activate mast cells to synthesize many different cytokines and chemokines, as well [5,7,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%